Origami contemporâneo: um estudo sobre a arte em dobra e sua mutabilidade prática - Teixeira, Samanta Aline [UNESP] (2015)
This article aims to seek new forms of creative and artistic expression origami nowadays. After crossing many generations and countries, we noted that the functions of origami are much broader than simply making folding paper: the folding has promoted a number of new buildings within the hybrid design and creativity. Modularity, the collective, the build conscious, contemporary and innovation are intrinsic relations to artistic praxis that configure an adjacent scenario and subordinate to the main structure that govern this research project. We believe in the essence of origami as a tangible functionality for creative thinking.